Effect of chronic exercise on immunoglobin, complement and leukocyte types in volleyball players and athletes - Saygin, Ozcan; Karacabey, Kursat; Ozmerdivenli, Recep; Zorba, Erdal; Ilhan, Fulya; Bulut, Vedat (Maghira & Maas Publications, 2006)
BACKGROUND: The objective of this study was to investigate the effect of various sports disciplines on basic elements of the acquired and natural defense systems and to compare their results with that of non-sporting controls. MATERIALS/METHODS: The study included 15 sedentary (Group1), 15 volleyball players (Group 2) and 15 long distance running athletes (Group 3). The VO2 Max for the groups was determined by subjecting the individuals to a 20 meter Shuttle run test. Immunoglobin and complement levels were measured by the turbidometric method. Leukocyte counts were made through peripheral blood smear examination. RESULTS: The IgA levels in sedentary living individuals was found to be lower than that in volleyball and athlete groups while that in athletes was in turn lower than that in volleyball players (p < 0.05). In volleyball players the IgG level was significantly higher than both the sedentary living individuals and the athletes (p < 0.05). IgM however, showed a significantly higher level in the sedentary group than in both athletes and volleyball players. The C3 levels in athletes was significantly lower than that of volleyball players and sedentary individuals (p < 0.05), while the C4 levels were higher in the volleyball group (p < 0.05). The leukocyte, eosinophil, and monocyte counts in the athletes were also significantly lower than those in the volleyball and sedentary groups (p < 0.05). The values for the sedentary group on the other hand however, was found to be lower than those of the volleyball players (p < 0.05). The neutrophil counts was lower in the sedentary group than in the volleyball group (p < 0.05). The levels in the athlete group was lower than that in the volleyball group, however (p < 0.05). The lymphocyte counts in volleyball players was higher than that in the sedentary group (p < 0.05). CONCLUSIONS: In conclusion, changes in the immune parameters were found to be dependent on the type of physical exercise performed on regular basis. Considering the protective antibody response in those performing regular sports, moderate exercise carried out on regular basis can be said to affect positively mononuclear and polymorphonuclear phagocytic cells - the basic elements of the natural immune system.
Keywords: volleyball; immune system; leukocyte; immunoglobulin